2022
DOI: 10.31616/asj.2022.0441
|View full text |Cite
|
Sign up to set email alerts
|

Management of Osteoporotic Vertebral Fracture: Review Update 2022

Abstract: A vertebral fracture is the most common type of osteoporotic fracture. Osteoporotic vertebral fractures (OVFs) cause a variety of morbidities and deaths. There are currently few “gold standard treatments” outlined for the management of OVFs in terms of quantity and quality. Conservative treatment is the primary treatment option for OVFs. The treatment of pain includes short-term bed rest, analgesic medication, anti-osteoporotic medications, exercise, and a brace. Numerous reports have been made on studies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 99 publications
(102 reference statements)
0
8
0
2
Order By: Relevance
“…Gründe hierfür sind zum einen die bestehenden Co-Morbiditäten des geriatrischen Patientenguts und zum anderen die Folgen der Frakturen an sich: chronische Schmerzen, verminderte Mobilität und damit auch Verlust der Selbstständigkeit, können den klinischen Verlauf stark beeinflussen. Ein weiteres großes Problem ist das Risiko für das Auftreten von Folgefrakturen, die dann zu einer weiteren Steigerung der Morbidität und auch Mortalität führen können [2,3].…”
Section: Osteoporotische Wirbelkörperfrakturenunclassified
See 1 more Smart Citation
“…Gründe hierfür sind zum einen die bestehenden Co-Morbiditäten des geriatrischen Patientenguts und zum anderen die Folgen der Frakturen an sich: chronische Schmerzen, verminderte Mobilität und damit auch Verlust der Selbstständigkeit, können den klinischen Verlauf stark beeinflussen. Ein weiteres großes Problem ist das Risiko für das Auftreten von Folgefrakturen, die dann zu einer weiteren Steigerung der Morbidität und auch Mortalität führen können [2,3].…”
Section: Osteoporotische Wirbelkörperfrakturenunclassified
“…Hierbei werden Fragilitätsfrakturen, bei denen Frakturen durch einen physiologischen Bewegungsumfang entstehen, die in einem gesunden Knochen nicht entstanden wären, von den traumatisch bedingten Frakturen unterschieden. Da auch in der Literatur beide Begriffe nicht eindeutig differenziert werden und häufig eine Mischverwendung stattfindet, wird im Weiteren der Begriff osteoporotische Wirbelkörperfraktur verwendet [3,4].…”
Section: Introductionunclassified
“…VCF by itself is a sign of bone weakness, and it requires a treatment to reverse the overall patient status and to prevent additional fractures from occurring; moreover, drugs acting on bone metabolism can play a role in patients' pain management [16] . Current drugs include bisphosphonates, calcitonin, estrogen, selective estrogen receptor modulators, parathyroid hormone, and receptor activators of nuclear factor kappa-B ligand inhibitor [17] .…”
Section: Multimodal Management Of Patients With Vfcmentioning
confidence: 99%
“…Analgesics are the first line in vertebral compression fracture treatment, generally administrating nonsteroidal anti-inflammatory drugs (NSAIDs). Opioids such as oxycodone can be combined with paracetamol for patients who do not respond well to first-line pain relievers [16] . Among antidepressants, Inhibitors of the Reuptake of Serotonin (SSRIs) can be used short-term in association with standard therapy to control pain in the acute phase in fragile patients; its main drawbacks are the risk of falling at high dosage and light sedation in chronic assumption [24] .…”
Section: Multimodal Management Of Patients With Vfcmentioning
confidence: 99%
“…S ince Galibert et al 1 first reported in 1984 among patients with an aggressive vertebral angioma, percutaneous vertebroplasty (PVP) has become the standard treatment for painful thoracolumbar osteoporotic vertebral compression fractures (OVCFs), OVCF osteonecrosis, vertebral pathologic fracture, and aggressive vertebral hemangioma, despite remaining a controversial procedure. [2][3][4][5][6] However, a substantial proportion of patients undergo PVP without an adequate intraoperative analgesic procedure, and procedural pain during PVP often tends to be overlooked in clinical practice. In addition, these procedures may result in painful experiences for patients.…”
mentioning
confidence: 99%